Are perceived barriers to accessing mental healthcare associated with socioeconomic position among individuals with symptoms of depression? Questionnaire-results from the Lolland-Falster Health Study, a rural Danish population study. Issue 3 (15th March 2019) - Packness, Aake; Halling, Anders; Simonsen, Erik; Waldorff, Frans Boch; Hastrup, Lene Halling
Abstract : Objective: To evaluate if perceived barriers to accessing mental healthcare (MHC) among individuals with symptoms of depression are associated with their socio-economic position (SEP). Design: Cross-sectional questionnaire-based population survey from the Lolland-Falster Health Study (LOFUS) 2016–17 of 5076 participants. Participants: The study included 372 individuals, with positive scores for depression according to the Major Depression Inventory (MDI), participating in LOFUS . Interventions: A set of five questions on perceived barriers to accessing professional care for mental health problem was posed to individuals with symptoms of depression (MDI score >20). Outcomes: The association between SEP (as measured by educational attainment, employment status and financial strain) and five different types of barriers to accessing MHC were analysed in separate multivariable logistic regression models adjusted for gender and age. Results: A total of 314 out of 372 (84%) completed the survey questions and reported experiencing barriers to MHC access. Worry about expenses related to seeking or continuing MHC was a considerable barrier for 30% of the individuals responding and, as such, the greatest problem among the five types of barriers. 22% perceived Stigma as a barrier to accessing MHC, but there was no association between perceived Stigma and SEP. Transportation was not only the barrier of least concern for individuals in general but also the issue with the greatest and most consistent socio-economic disparity (OR 2.99, 95% CI 1.19 to 7.52) for the lowest vs highest educational groups and, likewise, concerning E x penses (OR 2.77, 95% CI 1.34 to 5.76) for the same groups. Conclusion: Issues associated with Expenses and Transport were more frequently perceived as barriers to accessing MHC for people in low SEP compared with people in high SEP. Stigma showed no association with SEP. Informed written consent was obtained. Region Zealand's Ethical Committee on Health Research (SJ-421) and the Danish Data Protection Agency (REG-24–2015) approved the study.